The Impact of Forensic Accounting and Corporate Governance on Enhancing Accounting Transparency - Jabur, Hanan Salih (Journal of Economic, Administrative and Legal Sciences, 2025)
The aim of this research was to study the impact of forensic accounting and corporate governance principles. The relationship between the application of forensic accounting and corporate governance and their role in enhancing accounting transparency was analyzed. This was measured through the accuracy of accounting information, adherence to accounting standards, and full disclosure. Data was collected through a questionnaire that included 104 participants consisting of a sample of academics, accountants, and internal auditors at the General Company for Petrochemical Industries, as well as a sample of external auditors. Data was analyzed using statistical methods such as )Pearson’s correlation coefficient and simple linear regression(. The results showed that forensic accounting and governance play a significant role in enhancing transparency in accounting information. A strong significant relationship was found between the application of forensic accounting and governance and the accuracy of accounting information, with an impact coefficient of 0.917; compliance with accounting standards, with an impact coefficient of 0.872; and full disclosure, with an impact coefficient of 0.904. Based on these results, the researchers recommend strengthening the role of forensic accounting and governance by implementing legislation, improving the level of professional training, and activating the role of regulatory bodies to ensure compliance with governance standards and achieve accounting transparency.